2010
DOI: 10.4081/ejh.2010.e49
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical evidence of Muc1 expression during rat embryonic development

Abstract: During embryonic development, studies on mouse and human embryos have established that Muc1/MUC1 expression coincides with the onset of epithelial sheet and glandular formation. This study aimed therefore at evaluating the temporal and spatial expression of Muc1 at different stages of rat development. In this report, 80 animals were included: 64 rat foetuses at 13, 14, 15, 16, 17, 18, 19 and 20 days of gestation from pregnant females (WKAH/Hok), 8 embryos each stage. Standard immunohistochemistry was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Also high uptake in kidney organ during the time study were observed which is in agreement with the findings of Lacunza and coworkers 17 . This has already been shown by other groups, working with anti‐MUC1 probes 39–41 …”
Section: Discussionsupporting
confidence: 91%
“…Also high uptake in kidney organ during the time study were observed which is in agreement with the findings of Lacunza and coworkers 17 . This has already been shown by other groups, working with anti‐MUC1 probes 39–41 …”
Section: Discussionsupporting
confidence: 91%
“…The negative control was performed using isotype immunoglobulin G instead of the primary antibody. The positive control is small intestine from a 2‐week‐old male C57BL/6J mouse 47. Representative sections are shown.…”
Section: Resultsmentioning
confidence: 99%
“…Embryos and fetuses were obtained and processed according to previous studies (Lacunza et al, 2010). They were obtained by laparotomy and hysterectomy of the pregnant females.…”
Section: Tissue Processingmentioning
confidence: 99%
“…Immunohistochemistry was performed according to standard protocols as reported in a previous study (Lacunza et al, 2010). Briefly, dewaxed sections were treated with 10 mM sodium citrate buffer at 100 • C for 5 min for antigen retrieval and were placed in methanol with 0.3% H 2 O 2 to block endogenous peroxidase activity; after three washes in PBS, sections were blocked for non-specific binding with normal horse serum diluted 1:10 in 1% bovine serum albumin in PBS, (BSA)/PBS.…”
Section: Immunohistochemical Analysis (Ihc)mentioning
confidence: 99%